2019
DOI: 10.1007/s00125-019-05037-y
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to maternal obesity programs sex differences in pancreatic islets of the offspring in mice

Abstract: Aims/hypothesis Obesity during pregnancy increases offspring type 2 diabetes risk. Given that nearly half of women of child-bearing age in many populations are currently overweight/obese, it is key that we improve our understanding of the impact of the in utero/early life environment on offspring islet function. Whilst a number of experimental studies have examined the effect of maternal obesity on offspring islet architecture and/or function, it has not previously been delineated whether these changes are ind… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
51
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 55 publications
(71 reference statements)
9
51
0
1
Order By: Relevance
“…M displayed higher insulin levels than F but fasting insulin levels and the ratio of AUCins:AUCglc during the OGTT were reduced between MID and END in M. This demonstrate an improved liver metabolism in M between MID and END and would suggest that diet reversal post-weaning could partly rescue M from in utero changes. However, peripheral IS remained impaired in HF/C M at END, which could explain common diabetic phenotypes later in life, in line with the recent study 28 .…”
Section: Discussionsupporting
confidence: 88%
“…M displayed higher insulin levels than F but fasting insulin levels and the ratio of AUCins:AUCglc during the OGTT were reduced between MID and END in M. This demonstrate an improved liver metabolism in M between MID and END and would suggest that diet reversal post-weaning could partly rescue M from in utero changes. However, peripheral IS remained impaired in HF/C M at END, which could explain common diabetic phenotypes later in life, in line with the recent study 28 .…”
Section: Discussionsupporting
confidence: 88%
“…Human and animal studies have demonstrated the important role of in-utero and early postnatal environments in modulating offspring islet insulin secretion ( 13 16 ). This concept of the developmental origin of health and diseases (DOHaD) was first described by Dr. Barker and Dr. Osmond, where adults that experienced growth restriction during fetal life were found to have a higher rate of cardiovascular diseases during adulthood ( 17 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the sex-specific impact of maternal obesity exposure on insulin secretion in human offspring has not been studied extensively. Therefore, animal models have been used to delineate the specific impact of maternal obesity on offspring islet insulin secretion ( 16 , 26 , 27 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though there are numerous studies on the metabolic parameters of offspring of obese mothers (SAMUELSSON et al, 2007;DE OLIVEIRA ANDRADE et al, 2014;RIBAROFF et al, 2017;LOCHE et al, 2018;NICHOLAS et al, 2019), not many studies have explored the effect of maternal obesity in offspring weaned into an obesogenic diet (DE ALMEIDA FARIA et al, 2017; HUANG et al, 2020). There is, experimental studies have focused on the mismatch conceptthe effects of maternal obesity during gestation and lactation on offspring fed a control diet.…”
Section: Review Of the Literaturementioning
confidence: 99%